Genetic mapping of the chloroquine-resistance locus on Plasmodium falciparum chromosome 7. - Wellems, T E (1991)
The resurgence of malaria in recent decades has been accompanied by the worldwide spread of resistance to chloroquine, a drug once uncontested as the first-line antimalarial agent because of its efficacy and low toxicity. Chloroquine-resistant strains of Plasmodium falciparum counter the drug by expelling it rapidly via an unknown mechanism. In the absence of explicit biochemical knowledge of this efflux mechanism, reverse genetics provides a powerful approach to the molecular basis of chloroquine resistance. Here we report genetic linkage analysis in which 85 restriction fragment length polymorphism markers were used to examine inheritance of the 14 P. falciparum chromosomes in a laboratory cross between a chloroquine-resistant and a chloroquine-sensitive parasite. Inheritance data from 16 independent recombinant progeny show that the rapid efflux, chloroquine-resistant phenotype is governed by a single locus within an approximately 400-kilobase region of chromosome 7. Identification and characterization of genes within this region should lead to an understanding of the chloroquine-resistance mechanism.